Students' Perceptions of the Role of Parental Support in Increasing Interest in Learning Social Science at State Junior High School 10 Palu - Hanifa; Juraid; Misnah; Ika Nurjayanti (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to determine students' perceptions of the role of parental support on learning interest in social studies at SMP Negeri 10 Palu. To determine the influence of what form of parental support is perceived by students on learning interest in social studies at SMP Negeri 10 Palu. This population consists of all 5 classes of class VIII. Sampling using purposive sampling technique. Data collection techniques use interview and documentation processes. Based on the results of the study, the most influential form of maternal support on students' learning interest at SMP Negeri 10 Palu includes emotional support, motivational support, learning facilities, and loving supervision. Each form of support has a different impact, but all contribute to fostering learning interest. This support creates a pleasant learning atmosphere and makes children feel appreciated.